Pengembangan Jobsheet Alat Ukur dan Pengukuran Listrik berbasis Virtual Laboratory di Universitas Negeri Padang - Rahadi Ramlan; Fivia Eliza (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
This research is motivated by the application of online learning due to COVID-19, the implementation of academic activities in a pandami atmosphere at various universities eliminates face-to-face lectures and replaces them with online learning from home from various media. Jobsheet is a learning media for students to provide guidelines in completing a practicum. The purpose of this research is to develop jobsheets appropriate to use so as to improve the quality of the practicum lecture process and improve student understanding in mastering the lecture material. Types of research Research and Development (R&D) with a 4D development model consisting of Define, Design, Develop and Disseminate. Valid assessment jobsheet carried out by experts consisting of media experts and material experts, while practicality was assessed by lecturers and students, then for effectiveness seen from the results of practical learning when using jobsheet using Proteus 8 Professional software. The instrument collects data using a questionnaire. The results of this study were obtained jobsheets based on virtual laboratory based on media experts and material experts get valid categories. Practicality assessments assessed by course lecturers are categorized as very practical, then practicality assessments from students are categorized as very practical. Assessment of the effectiveness of the results of the practicum is categorized as effective. So that jobsheets developed can be used by lecturers to convey material in practical learning activities.